2013
DOI: 10.1002/jmri.24453
|View full text |Cite
|
Sign up to set email alerts
|

Ultrashort Echo Time (UTE) imaging of receptor targeted magnetic iron oxide nanoparticles in mouse tumor models

Abstract: Purpose: The purpose of this study was to investigate an ultrashort echo time (UTE) imaging approach for improving the detection of receptor targeted magnetic nanoparticles in cancer xenograft models using positive contrast. Materials and Methods: Iron oxide nanoparticle (IONP) conjugated with tumor targeting ligands were prepared. A 3D UTE gradient echo sequence with the shortest TE of 0.07 msec was evaluated on a 3T magnetic resonance imaging (MRI) scanner using IONP solution, cancer cells bound with targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 43 publications
0
28
0
Order By: Relevance
“…Thus, T 1 signal is dominated and gives rise to bright T 1 MRI contrast as demonstrated in vitro and in vivo by sub-5-nm core size ultrafine IONPs reported by Huang et al [18]. Understanding the interplay between T 1 and T 2 contrast at different core sizes, one can use ultrashort echo time MRI sequence to obtain bright T 1 contrasts with larger sized IONPs as demonstrated in the study in which the accumulation of 10-nm core size IONPs can be observed with ultrashort TE MRI with bright T 1 contrast in orthotopic pancreatic tumors following systemic delivery [55]. To obtain the highest magnetism under size of 100 nm, a recent report showed that 65-nm Fe 3 O 4 nanospheres presented the strongest saturation magnetization (89.24 emu/g) and microwave reflection loss (-30.37 dB at 9.68 GHz), compared with other IONPs at different sizes [56].…”
Section: Sizementioning
confidence: 96%
“…Thus, T 1 signal is dominated and gives rise to bright T 1 MRI contrast as demonstrated in vitro and in vivo by sub-5-nm core size ultrafine IONPs reported by Huang et al [18]. Understanding the interplay between T 1 and T 2 contrast at different core sizes, one can use ultrashort echo time MRI sequence to obtain bright T 1 contrasts with larger sized IONPs as demonstrated in the study in which the accumulation of 10-nm core size IONPs can be observed with ultrashort TE MRI with bright T 1 contrast in orthotopic pancreatic tumors following systemic delivery [55]. To obtain the highest magnetism under size of 100 nm, a recent report showed that 65-nm Fe 3 O 4 nanospheres presented the strongest saturation magnetization (89.24 emu/g) and microwave reflection loss (-30.37 dB at 9.68 GHz), compared with other IONPs at different sizes [56].…”
Section: Sizementioning
confidence: 96%
“…As a result, positive T 1 contrast for imaging and quantifying IONPs in tissues has not been widely used. However, sequences like sweep imaging with Fourier transformation (SWIFT) and ultrashort echo‐time (UTE) have recently demonstrated utility for detecting and quantifying high IONP concentrations with positive contrast at relatively high iron concentrations. These sequences have a negligible T 2 or normalT2* weighting because they acquire signal immediately during or after the excitation pulse.…”
Section: Introductionmentioning
confidence: 99%
“…41,127 Systemic delivery of uPAR-targeted IONPs led to an accumulation of IONPs in tumors of Balb/c mice bearing 4T1 mouse mammary tumor or nude mice bearing MDA-MB-231 tumor xenografts and generated strong MRI T 2 contrast for tumor MRI. 41 We further demonstrated targeted delivery of NIR dye-labeled IONPs into mice bearing breast tumor xenografts enabling noninvasive multimodal tumor imaging by NIR optical, T 2 -weighted or ultra-short TE MRI, 3D fluorescence tomography, and photoacoustic tomography [128][129][130] (Figure 5). uPAR-targeted nanoprobes significantly enhanced photoacoustic contrast of the tumor margins compared with nontargeted groups, with imaging to depths up to 31 mm.…”
Section: Magnetic Iron Oxide Nanoparticles (Ionps)mentioning
confidence: 92%
“…Prussian blue staining of the tumor tissue section showed the presence of blue nanoparticle positive cells in the tumor (h). Reproduced and modified with the permission of John Wiley and Sons Inc [126]. B.…”
Section: Figurementioning
confidence: 99%